Protein kinase C isozyme expression in right ventricular hypertrophy induced by pulmonary hypertension in chronically hypoxic rats - Zeng, Chao (Mol Med Rep, 2017)
In chronic hypoxia, pulmonary hypertension (PH) induces right ventricular hypertrophy (RVH). Evidence indicates that protein kinase C (PKC) serves a crucial role in hypoxia-induced RVH. The present study investigated PKC isoform-specific expression and its involvement in RVH. Rats were exposed to normobaric hypoxia for a number of days to induce PH. PKC isoform-specific membrane translocation and protein expression in the myocardium were evaluated by western blotting and immunostaining. A total of six isoforms of conventional PKC (cPKC; α, βI and βII) and of novel PKC (nPKC; δ, ε and η), were detected in the rat myocardium. Hypoxic exposure (1–21 days) induced PH with RVH and vascular remodeling. nPKCδ membrane translocation at 3–7 days and cPKCβI expression at 1–21 days in the RV following hypoxic exposure were significantly decreased as compared with the normoxia control group. Membrane translocation of cPKCβII at 14–21 days and of nPKCη at 7–21 days in the left ventricle following hypoxic exposure was significantly increased when compared with the control. The results of the present study suggested that the alterations in membrane translocation, and nPKCδ and cPKCβI expression, are associated with RVH following PH, and the upregulation of cPKCβII membrane translocation is involved in left-sided heart failure.